APPLICATION OF SCHOOL LITERACY MOVEMENT PROGRAM (GLS) IN ELEMENTARY SCHOOL MATHEMATICS LEARNING - Novy Trisnani (Universitas Sebelas Maret, 2018)
The School Literacy Movement Programis a form of government concern for the low competency of Indonesian students in the fields of mathematics, science, and reading. The implementation of GLS in learning in elementary schools is carried out in four stages, preparation, implementation, monitoring, and evaluation stages. GLS at the preparation stage in mathematics learning, including the provision of integrated mathematics learning based on literacy, and at the implementation stage are structured literacy learning classes, and the organization of literacy-based mathematics materials. The application of GLS in learning mathematics in elementary school is very important to build students 'understanding, writing skills, and communication skills by increasing understanding of reading texts in all subjects and improving students' high thinking skills (Higher Order ThinkingSkill/HOTS).